AÇÕES ANTI - INFLAMATÓRIA E ANTINOCICEPTIVA DO EXTRATO ETANÓLICO DE Hymenaea courbaril L. EM ROEDORES - Brito, Fernando Cesar Rodrigues; Cunha, Luana Mara Silva De Castro Pacheco da; Gonçalves, Danilo Oliveira; Olinda, Tiago Moreira (Ciência Animal, 2024)
The anti-inflammatory and antinociceptive actions of the Ethanolic Extract from Hymenaea courbaril L. (EEHC) were evaluated for the first time in animal models. The extract was produced using the stem bark. The preparation was administered to rodents per orally. EEHC has efficiently reduced the abdominal contortions induced by acetic acid; time of paw licking in formalin test; paw edema induced by carrageenan and dextran; leukocyte migration after intraperitoneal injection of carrageenan and myeloperoxidase expression on peritoneal exudate. EECH also improved the histopathological damage in the rat paw after carrageenan inflammation as well as reduced TNF-a expression in the scabies tissue. Doses ranging from 1 to 400 mg/kg were tested. The dose of 100 mg/kg presented significant results in ali experiments (p < 0.05). The data suggests intense anti-inflammatory and antinociceptive effects associated to extract from Hymenaea courbaril. Further studies must be carried out to elucidate the mechanisms involved.